(untitled) (REMUNOM, 2025)
The article analyzes female participation in Computing courses at Higher Education Institutions in Alagoas (2019-2023) and discusses strategies to increase their presence in the field, based on initiatives identified in the Women in Information Technology Proceedings (2020-2024). Despite progress in female inclusion in the job market, women’s representation in the field remains low, reflecting historical and cultural challenges. This study identifies factors such as the lack of female role models, gender stereotypes, and unequal encouragement from childhood. In addition to mapping gender distribution in these courses, the study discusses initiatives to expand female participation in Computing, contributing to a more equitable and inclusive academic environment.